Examining the Dual Nature of Divorce Trial Cases In Indonesia: Private Hearings and Public Verdicts - Tanjung, Afriansyah; Riskanita, Dinda; Rizal, Muhammad (Fakultas Hukum Universitas Widya Mataram, 2025)
This article explores the dual procedural character of divorce trials in Indonesia, wherein court examinations are mandated to be private while the final judgment must be publicly announced. Triggered by the controversy in the divorce case of Baim Wong and Paula Verhoeven, the study emphasizes the urgency of reinforcing judicial compliance with both transparency and privacy protections. Employing a normative juridical method based on secondary data, including statutory regulations and doctrinal analysis, the research assesses the intersection between Law No. 48 of 2009 on Judicial Power and Law No. 14 of 2008 on Public Information Disclosure. The findings indicate that while judicial decisions are inherently public, sensitive personal information revealed during closed hearings must be exempted from disclosure. The case underscores the necessity for clearer procedural boundaries to ensure that the judiciary maintains both public accountability and the protection of individual rights in family law cases.